ANALISIS PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN VARIABEL KEUANGAN TERHADAP NILAI PERUSAHAAN - Bahriyah Eka Musha Bakti; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine and test whether the mechanism of good corporate governance (board of commissioners, independent commissioners, institutional ownership, managerial ownership and audit committee) and financial variables were measured by financial ratios such as liquidity, leverage, profitability and activity. have an influence on firm value. In property and real estate sub-sector companies listed on the Indonesia Stock Exchange. This study uses 135 property and real estate sub-sector companies listed on the Indonesia Stock Exchange which were selected using the purposive sampling method in the period 2018 to 2020. The data in this study were analyzed using the multiple linear regression analysis method. The results of this study indicate that the board of commissioners, institutional ownership, and activities have an effect on firm value. Meanwhile, independent commissioners, managerial ownership, audit committee, liquidity, leverage, and profitability have no effect on firm value.